A cross sectional study on the levels of knowledge, attitude and preventive practices of hypertension among residents aged 18 years and above in Kampung Baru Ixora, Sarikei - Pak Inn, Teoh; Kia Sing, Tan; Siew Peng, Tew; Suhaib B., Mohd Amin; Nur Muhammad Kamil B., Abdullah; Nur Jalilah Bt., Ahmad Khazali; Nor Nazuha Bt., Mohamad; Normina Bt. c, Ahmad Bustami; Noor Aishah Bt., Yussof; Mohd. Anwar B., Ibrahim; Chiu Yee, Liew; Huey Chun, Lee; et al. (Universiti Malaysia Sarawak, (UNIMAS), 2006)
Hypertension is a highly prevalent non-communicable disease which is controllable through risk factor modification and anti-hypertensive medication. It remained a public health problem due to lack of awareness of individuals to modify risk factors and live a healthy lifestyle. The objective of this study was to study the level of knowledge, attitude and preventive practices of hypertension among residents aged 18 years and above in Kampung Baru Nora, Sarikei from 26`x' June 2006 to I5` September 2006. The level of knowledge, attitude and preventive practices were assessed in relation to their age, gender, education level, household income, status of being diagnosed with hypertension and family history of hypertension. A cross-sectional study was carried out with a sample population of 101 respondents chosen by simple random sampling method. Interview-guided questionnaire was conducted and data entry and analysis were done using SPSS version 13 software. The results showed that 52.5% of the respondents had adequate knowledge, 57.4% had positive attitude and 61.4% of them had good preventive practices of hypertension. Analysis revealed that there was a significant association between the level of knowledge with education level and family history of hypertension (Mann-Whitney test, p< 0.05). For the attitude, there was a significant difference between the level of attitude and education level (Mann-Whitney test, p< 0.05). As for the preventive practices, there was a significant difference in proportion of its level in the different age group (x2df==2=9.567p,< 0.05). Significant difference was also found between the level of preventive practices and status of being diagnosed with hypertension (Mann-Whitney test, p< 0.05). Moreover, significant relationships were found between the level of knowledge and attitude (Spearman's rho= 0.309, p< 0.05) and between the level of attitude and the level of preventive practices (Spearmen's rho= 0.258, p< 0.05). Furthermore, the level of knowledge and preventive practices had a significant difference in proportions (x`dFi = 5.760, p< 0.05). The results were comparable to study by Muntner et al. (2004) which stated that there was a significant relationship between the education level and the level of knowledge, and 50.2% respondents who were aware of their hypertension modified their lifestyle. The education level had an influence on the level of knowledge and attitude while the level of preventive practices was influenced by age group. It is recommended that the respondents need further health education to increase their level of knowledge, attitude towards risk factor modification and sports activities to increase their level of preventive practices. Further studies on knowledge, attitude and practices of hypertension should be done.